Stories of the Forgone Forlorn Forgotten Space: Interrogating Mdantsane’s Liminal Space in which Ritual Operates - Xhegwana, Buhle (University of the Witwatersrand, Johannesburg, 2023)
The proposed site is located on Golden Highway in Mdantsane, Eastern Cape, and is a vacant plot of land adjacent to Mdantsane Correctional Services. The site situates itself in close proximity to multiple educational institutions and commerce, centrally within the township. The proposed research aims to analyse how Amasiko (cultural practices and their memory) within a non-transcribed culture can be translated into a built form that would be representative of its people. The built form would be envisioned as a container for memory where the ethnographic layering of information becomes a tool to access the ritual and its memory as a “Grand Mnemonic Device” to relay import ant aspects of the culture and its history (Trieb, 2013). The space envisaged must promote the acts of remembering and collecting as a tool in the process of creating a “house of memory” (Bahloul, 1992). This assembles what was not transcribed into a physical, experiential manifestation by creating a stronger link between architecture and society, looking beyond the merely functional state of architecture represented in the context. The program enacted in the space will mirror the act of the ritual by providing spaces that relate to the processes of the ritual in their various stages of the procession. The three main ritual processes focused on include Umgidi (Initiation ceremony), Umshado (wedding) and Umngcwabo (Funeral). The spaces proposed function as a tool to access the memory and ritual through its organisation while its program reaches out to the community. The program includes a community hall centred around the acts of song, dance and sermon; a kitchen to be used during gatherings and as a link to food security outreach; urban farm facilities to service the kitchen and community; discussion rooms for skill sharing, dialogue, non-transcribed learning and storytelling; video exhibition spaces to immerse oneself in the memory; a foyer with a primary focus on cleansing or washing hands before crossing the threshold into the space; storage and offices for facilitators of the space.
A research report proposal submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Architecture (Professional).
Keywords: Golden Highway; Mdantsane; Eastern Cape; Mdantsane Correctional Services; Amasiko (cultural practices and their memory); Grand Mnemonic Device; Trieb, 2013; Bahloul, 1992; Umgidi (Initiation ceremony; Umshado (wedding); Umngcwabo (Funeral; SDG-4: Quality education